N, N-Dimethyl Leucines as Novel Isobaric Tandem Mass Tags for Quantitative Proteomics and Peptidomics - Xiang, Feng (2010)
Herein we describe the development and application of a set of novel N, N-dimethyl leucine (DiLeu) 4-plex isobaric tandem mass (MS(2)) tagging reagents with high quantitation efficacy and greatly reduced cost for neuropeptide and protein analysis. DiLeu reagents serve as attractive alternatives for isobaric tag for relative and absolute quantitation (iTRAQ) and tandem mass tags (TMTs) due to their synthetic simplicity, labeling efficiency and improved fragmentation efficiency. DiLeu reagent resembles the general structure of a tandem mass tag in that it contains an amine reactive group (triazine ester) targeting the N-terminus and ε-amino group of the lysine side-chain of a peptide, a balance group, and a reporter group. A mass shift of m/z 145.1 is observed for each incorporated label. Intense a(1) reporter ions at m/z 115.1, 116.1, 117.1, and 118.1 are observed for all pooled samples upon MS(2). All labeling reagents are readily synthesized from commercially available chemicals with greatly reduced cost. Labels 117 and 118 can be synthesized in one step and labels 115 and 116 can be synthesized in two steps. Both DiLeu and iTRAQ reagents show comparable protein sequence coverage (~43%) and quantitation accuracy (<15%) for tryptically digested protein samples. Furthermore, enhanced fragmentation of DiLeu labeling reagents offers greater confidence in protein identification and neuropeptide sequencing from complex neuroendocrine tissue extracts from a marine model organism, Callinectes sapidus.